Protonation and coordinative properties of 14-membered tetraaza macrocycles linked to phthalocyanines - Avciata, U; Bozdogan, AE; Koçak, M; Gül, A; Okur, AI; Bekaroglu, Ö (SPRINGER-VERLAG WIEN, 1999)
The protonation behaviour and coordination ability of 14-membered tetraaza macrocycles in the periphery of a phthalocyanine core (L) together with a model compound of identical macrocyclic structure towards Co2+, Ni2+, and Cu2+ has been studied potentiometrically at 25 degrees C in 0.3M KCl solution. The protonation pattern of L indicates that the basicities of three secondary amino groups are high and comparable; the fourth one is of rather low basicity, probably due to the effect of charge repulsion. It is shown that the potentiometric data for the phthalocyanine derivative can be used to estimate the stability constants and the distribution diagram for the species in solution by treating each macrocycle L' at the periphery of the phthalocyanine core separately using the program TITFIT.
Keywords: phthalocyanine; tetraaza macrocycles; stability constants; METAL-COMPLEXES; LIGANDS; Chemistry